PERSPEKTIF HUKUM EKONOMI SYARIAH TERHADAP SISTEM TAKARAN PENJUALAN PREMIUM SECARA ECERAN DI SUKOREJO SITUBONDO - Misbahul Ali (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2021)
Dosage is defined as a process of measuring to find out the level, weight, or price of certain goods. In the process of measuring activities, it is known as measuring. Measuring is often equated with weighing. Measuring or weighing is part of the trade that is often done by traders. Traders usually use tools to measure such as cans, hands, bottles, and others. While the tool used to weigh is a scale which is also called a balance because it has a balance. Measures and scales are two kinds of measuring tools that pay attention to being used properly and correctly in the perspective of Islamic economics. In this paper, it is concluded that the implementation of the premium dosing system in retail is allowed because it does not contain elements of Gharar due to the willingness of the buyer. Buyers also feel helped by the premium retail because they don't have to bother queuing at the gas station, while the seller only takes a little profit with the willingness of the buyer